2019
DOI: 10.1590/1983-21252019v32n306rc
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxychloride Applied Alone to Control Citrus Black Spot

Abstract: Citrus black spot (CBS) is a disease caused by the Phyllosticta citricarpa fungus that causes lesions in fruits and, in more severe stages, fruit drops. The use of systemic fungicides is the main control measure for CBS; however, an alternative control measure is the use of cupric fungicides applied alone with short intervals. Therefore, the objective of the present work was to evaluate the effect of applications of copper oxychloride at different rates on the control of CBS. The experiment was conducted in Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…These results corroborate other studies that observed higher efficiency of QoI compared to copper-based fungicides (Miles et al, 2004;Silva Junior et al, 2016b). Fixed copper compounds (Frac group M1) act non-specifically at the cell membrane level and once inside the cells, they interfere with numerous enzymatic reactions, with consequent inhibition of spore germination (La Torre et al, 2018) and thereby prevent the fungal pre-penetration steps and disease progress (Fonseca et al, 2019). QoI fungicides or strobilurins act as respiration inhibitors by binding to mitochondrial cytochrome b (complex III), disrupting ATP production (Olaya et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate other studies that observed higher efficiency of QoI compared to copper-based fungicides (Miles et al, 2004;Silva Junior et al, 2016b). Fixed copper compounds (Frac group M1) act non-specifically at the cell membrane level and once inside the cells, they interfere with numerous enzymatic reactions, with consequent inhibition of spore germination (La Torre et al, 2018) and thereby prevent the fungal pre-penetration steps and disease progress (Fonseca et al, 2019). QoI fungicides or strobilurins act as respiration inhibitors by binding to mitochondrial cytochrome b (complex III), disrupting ATP production (Olaya et al, 1998).…”
Section: Discussionmentioning
confidence: 99%